2012
DOI: 10.1007/s00701-012-1501-3
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of 2-mercaptoethane sulfonate (MESNA) against traumatic brain injury in rats

Abstract: Although further studies considering different dose regimens and time intervals are required, MESNA was shown to be at least as effective as methylprednisolone in the traumatic brain injury model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…[ 6 ] However, the planned dose of the application in neurotologic surgery is not that high and former animal studies suggest the neuroprotective feature of systemic MESNA application. [ 2 11 ] A single dose of 150 mg/kg MESNA was shown to decrease the apoptotic activity (caspase-3 activity) in the spinal cord following ischemia/reperfusion injury in a rabbit model. [ 2 ] In another study, MESNA increased the levels of the antioxidant enzymes (glutathione peroxidase and superoxide dismutase), decreased oxidative enzymes and molecules (nitric oxide, nitric oxide synthetase, and xanthine oxidase) and protected the brain tissue histopathologically with systemic administration immediately after the brain injury in rat models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 ] However, the planned dose of the application in neurotologic surgery is not that high and former animal studies suggest the neuroprotective feature of systemic MESNA application. [ 2 11 ] A single dose of 150 mg/kg MESNA was shown to decrease the apoptotic activity (caspase-3 activity) in the spinal cord following ischemia/reperfusion injury in a rabbit model. [ 2 ] In another study, MESNA increased the levels of the antioxidant enzymes (glutathione peroxidase and superoxide dismutase), decreased oxidative enzymes and molecules (nitric oxide, nitric oxide synthetase, and xanthine oxidase) and protected the brain tissue histopathologically with systemic administration immediately after the brain injury in rat models.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] In another study, MESNA increased the levels of the antioxidant enzymes (glutathione peroxidase and superoxide dismutase), decreased oxidative enzymes and molecules (nitric oxide, nitric oxide synthetase, and xanthine oxidase) and protected the brain tissue histopathologically with systemic administration immediately after the brain injury in rat models. [ 11 ] These studies showed the neuroprotective effect of MESNA by enzyme systems as a systemic one dose regimen (150 mg/kg) with a short exposure interval (24 h). In guinea pig models, the otologic effects of 10 or 20% of MESNA application locally to the middle ear were analyzed, no toxic effect of MESNA was seen on cochlear morphology or inner ear.…”
Section: Discussionmentioning
confidence: 99%
“…[13] The expression of proinflammatory cytokines at the site of injury, including IL-1β and TNF-α, regulate precise cellular events that occur within the first few hours of TBI and persist in the neural tissue for several days with cytokines also being detectable on microglia, perivascular macrophages, and astrocytes. [14,15] Most important secondary factors leading to further neuronal death are lipid peroxidation, apoptosis, and development of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Acetaminophen-induced liver injury is associated with significant formation of acrolein, and treatment of mice with MESNA significantly reduces acetaminophen-induced liver injury and acrolein adduct formation [80]. Traumatic brain injury is associated with extremely high levels of RCS and MESNA treatment markedly reduced RCS levels and protected brain tissue in rats subjected to traumatic brain injury [81]. Clinical trials are needed to confirm the efficacy of MESNA against these same conditions in humans.…”
Section: Reactive Carbonyl Species Scavengers Ameliorate Diseasementioning
confidence: 99%